Oral Steroid Usage for Otitis Media with Effusion, Eustachian Tube Dysfunction, and Tympanic Membrane Retraction. (29th March 2016) - Bellmunt, Angela M.; Vila, Peter M.; Chen, Jenny X.; Rosenfeld, Richard M.; Hackell, Jesse M.; Shin, Jennifer J.
Abstract : Objectives: Avoiding oral steroids for otitis media with effusion (OME) is endorsed as a performance measure by the National Quality Foundation, but data regarding current gaps and practice patterns are lacking. Our objectives were to evaluate oral steroid use for OME and the related diagnoses of eustachian tube dysfunction (ETD) and tympanic membrane retraction (TMR), to assess variations by visit setting, and to identify opportunities for measurable performance improvement. Study Design: Cross‐sectional analysis of a national database. Setting: Ambulatory visits in the United States. Subjects: Children and adults in the National Ambulatory Medical Care Survey and the National Hospital Ambulatory Medical Care Survey (2005‐2010). Methods: Data were coded for patient demographic information, potential confounders (eg, concurrent conditions managed by oral steroids), and diagnosis of OME, ETD, or TMR (OME/ETD/TMR). The latter 2 diagnoses were included to meet minimum numbers for reliability of weighted estimates, but OME constituted the majority of cases. Multivariate regression was used to determine the variables associated with oral steroid use. Results: Among 590, 772 observations representing 7, 191, 711, 480 visits for OME/ETD/TMR, 3.2% resulted in a new prescription for oral steroid medication (2.3% for children, 7.0% for adults). Adults were more likely to receive steroids (odds ratio = 3.50, P <. 001) than those with other diagnoses, but a similar association was not found for children. Patients seen by an otolaryngologist or in the emergency department were less likely to receive steroids than those seen in other settings. Conclusions: OME/ETD/TMR is infrequently treated with oral steroids, particularly in children. Opportunities for performance improvement are limited.